Infrared thermography detection of grouting defects in external post-tensioned tendon ducts under construction hydration heat excitation. (March 2023) - Li, Shengli; Han, Shanling; Wang, Jiangfei; Han, Xiaolei; Zheng, Pengfei; Cui, Can; Gao, Xing; Sun, Shiji
Abstract: Most duct grouting defects are caused during the construction period, and its existence will seriously affect the safety performance of the structure. Timely detection and remediation during the construction period will reduce the high inspection and maintenance costs and the probability of structural failure later. This study proposed an approach for detecting grouting defects in external post-tensioned tendon ducts using infrared thermography (IRT) under the hydration heat of duct grouting material. IRT semi real-time detection of four different grouting defect specimens was performed indoors in the first 48 h after grouting completion to validate the proposed approach. Results showed that grouting defects with 0%, 40%, and 70% grouting compactness in high-density polyethylene ducts could be identified simultaneously from 12 h to 21.5 h after grouting completion, while defects in galvanized steel pipes (GSP) could also be identified after improving the emissivity and reflectivity of the pipe surface. Furthermore, grouting compactness could be quantified by the distance between the half maximum contrast, and PCA-based image preprocessing could reduce the quantitative error of grouting compactness detection. In addition, the detection in high temperature environment should be avoided because the rise in ambient temperature would reduce the identification ability of grouting defects. IRT technique could guide the grouting construction of external tendon ducts in actual engineering because of its ability to efficiently identify grouting defects during the hydration heat release stage of grouting material.